An architecture for MPEG-21 based live adaptation of H264 video - Iqbal, Razib (University of Ottawa (Canada), 2006)
Diversity of devices in both wired and wireless networks through which multimedia contents are desired to be accessed and interacted with has grown significantly. The driving concept of Universal Multimedia Access (UMA) depicts that instead of having multiple types of the same content, it is preferred to adapt the original content accordingly. Conventional transcoders adapt digital contents by decompression, adaptation, and recompression. An easy solution to adaptation is thus achieved by allocating some trusted intermediary nodes in between the media resource provider and the consumer to perform manifold decoding and encoding operations. But if cascaded transcoding can be avoided and adaptation can be performed in a compressed domain without decompression and re-compression, it will be surely a significant improvement. The objective of this thesis is to show that knowledge of the bitstream along with content structure in the form of MPEG-21 generic Bitstream Syntax Description (gBSD) enables the adaptation process to be easily deployable avoiding cascaded transcoding. A comprehensive study and an implementation technique of a dynamic schema for temporal adaptation of the H.264 pre-recorded and live video, conforming ISO/IEC MPEG-21 Digital Item Adaptation (DIA), is presented in this work. Adaptation is performed on demand directly from the bitstream and its gBSD. As a result, any MPEG-21 compliant host can adapt the stream without requiring the video codec.
Keywords: Computer Science.